Emerging virus diseases: can we ever expect the unexpected? - Colin R Howard; Nicola F Fletcher (Emerging Microbes and Infections, 2012)
Emerging virus diseases are a major threat to human and veterinary public health. With new examples occurring approximately one each year, the majority are viruses originating from an animal host. Of the many factors responsible, changes to local ecosystems that perturb the balance between pathogen and principal host species is one of the major drivers, together with increasing urbanization of mankind and changes in human behavior. Many emerging viruses have RNA genomes and as such are capable of rapid mutation and selection of new variants in the face of environmental changes in host numbers and available target species. This review summarizes recent work on aspects of virus emergence and the current understanding of the molecular and immunological basis whereby viruses may cross between species and become established in new ecological niches. Emergence is hard to predict, although mathematical modeling and spatial epidemiology have done much to improve the prediction of where emergence may occur. However, much needs to be done to ensure adequate surveillance is maintained of animal species known to present the greatest risk thus increasing general alertness among physicians, veterinarians and those responsible for formulating public health policy.Emerging Microbes & Infections (2012) 1, e46; doi:10.1038/emi.2012.47